Inhibitory Effect of an Ellagic Acid-Rich Pomegranate Extract on Tyrosinase Activity and Ultraviolet-Induced Pigmentation - Mineka Yoshimura (2005)
Inhibitory Effect of an Ellagic Acid-Rich Pomegranate Extract on Tyrosinase Activity and Ultraviolet-Induced Pigmentation